Odpowiedź :
Odpowiedź:
a) 4x - 6 = 26
4x = 26 + 6
4x = 32
x = 8
b) -4 + 4x = -28
4x = -28 + 4
4x = -24
x = -6
c) -5x - 8 = 27
-5x = 27 + 8
-5x = 35
x = -7
d) 3y + 4 = 19
3y = 19 - 4
3y = 15
y = 5
e) 2 + 7a = 44
7a = 44 - 2
7a = 42
a = 6
f) -2x - 13 = 1
-2x = 1 + 13
-2x = 14
x = -7
g) 4x - 8 = 12
4x = 12 + 8
4x = 20
x = 5
h) 2y + 10 = 2
2y = 2 - 10
2y = -8
y = -4
i) 5 - 6x = -13
-6x = -13 - 5
-6x =18
x = -3
j) 9x - 12 = 6
9x = 6 + 12
9x = 18
x = 2
k) 7x - 14 = 14
7x = 14 + 14
7x = 28
x = 4
l) 2 + 5a = -23
5a = -23 - 2
5a = -25
a = -5
Szczegółowe wyjaśnienie:
d) 3y+4=19
3y=15
y=5
e) 2+7a=44
7a=42
a=6
f)-2t-13=1
-2t=14
t= -7
g) 4x-8=12
4x=20
x=5
h) 2y+10=2
2y=8
y=4
i) 5-6x= - 13
-6x =-18
x=3
j) 9x-12 =6
9x=18
x=2
K) 7x-14=14
7x =28
x=4
L) 2+5x =-23
5x=-25
x=-5